2020
DOI: 10.1177/0040517519900385
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of boron nitride nanosheets using a chemical exfoliation method as a thermal conductive filler for the development of silicone thermal pads: Part II: Optimization of process parameter design on the development of a silicone thermal pad

Abstract: This study developed a silicone thermal pad with high thermal conductivity and high mechanical properties. Boron nitride nanosheets (BNNSs) with different lamella thicknesses were prepared in Part I and Al2O3 was filled with silicone rubber to prepare silicone thermal pads. The silicone thermal pads were prepared using the Taguchi method and the elimination and choice translating reality method. BNNSs with different lamella thicknesses, BNNS loading level, and Al2O3 loading level were set as control factors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Silicone rubber composites in such pads exhibit excellent thermal conductivity with the incorporation of BN as a filler using a simple sol-gel process for surface modification. Kuo et al 21 synthesized silicone thermal pads using the Taguchi method and concluded that the optimum experimental combination was BNNS with lamella thickness (B 24 ), a BNNS loading (controlling factor) level of 20 wt%, and an aluminum oxide (Al 2 O 3 ) loading level of 60 wt%. The thermal conductivity, tensile strength, and shore hardness of the silicone thermal pads, which were prepared by thermosetting, were 5.25 Wm/K, 7.55 kg/cm 2 and 65.2 (shore A), respectively.…”
mentioning
confidence: 99%
“…Silicone rubber composites in such pads exhibit excellent thermal conductivity with the incorporation of BN as a filler using a simple sol-gel process for surface modification. Kuo et al 21 synthesized silicone thermal pads using the Taguchi method and concluded that the optimum experimental combination was BNNS with lamella thickness (B 24 ), a BNNS loading (controlling factor) level of 20 wt%, and an aluminum oxide (Al 2 O 3 ) loading level of 60 wt%. The thermal conductivity, tensile strength, and shore hardness of the silicone thermal pads, which were prepared by thermosetting, were 5.25 Wm/K, 7.55 kg/cm 2 and 65.2 (shore A), respectively.…”
mentioning
confidence: 99%
“…17 Kuo et al. 18 synthesized STPs by using the Taguchi method and thereafter the elimination and choice translating reality method, and investigated the effect of the different sets of control factors on the thermal conductivity, tensile property, and hardness of the STPs to determine the optimum product optimization process parameters. The thermal conductivity and tensile strength of the STPs were 5.25Wm −1 K −1 and 7.55 kg/cm 2 with 34.48% and 20.26%, respectively.…”
mentioning
confidence: 99%